Terapi Perilaku Kognitif Terhadap Pasien Depresi Pasca Stroke di Kota Palangka Raya - Maria Magdalena Purba; Christine Aden (STIKes Hang Tuah Pekanbaru, 2021)
Post-stroke depression is found to be around 20-65%, this prevalence shows a high enough number. Lack of attention to post-stroke depression causes the patient's condition worsen, while appropriate intervention and treatment of depression can benefit healing and even shorten the rehabilitation process. This study aims to determine the effect of cognitive-behavioral therapy on post-stroke depression patients in the city of Palangka Raya. The method of this research is quantitative research with a type of pre-test post-test control group design research with a total sample of 50 post-stroke depression patients divided into two groups: the treatment group and the control group. Kuesinoer in this study used the Hamilton scale instrument (HDRS) consisting of 20 questions to measure the level of depression in post-stroke patients. In the treatment group, cognitive behavioral therapy intervention sessions session 1-4 were given with two meetings. Data analysis in this study was carried out through univariate and bivariate analysis with paired t-tests. The results showed that there were significant differences in the average value of depression rates of post-stroke patients in the treatment group before and after cognitive behavior therapy with p <0.05 and IK did not exceed zero. It is expected that nurses can become educators, motivators, and facilitators as well as family support systems in treating post-stroke depression patients